Late Roman and early Byzantine pottery from Saldum: Reflection of change in social and historical circumstances - Jeremić, Gordana (Rei Cretariae Romanae Fautorum Acta, 2012)
Gradac-Saldum archaeological site is located in the village of Dobra, in eastern Serbia, at the entrance to Gornja Klisura (Upper Gorge) in Djerdap area, about 130 Roman miles downstream from Singidunum or about 70 miles from Viminacium. the site is about 350 m upstream from the confluence of the Kožica brook and the Danube. the modern settlement of Berzasca lies opposite Saldum, at the confluence of the Valea mare and the Danube, at the spacious river plateau, where a larger settlement was situated in Roman times.